Educational Marketing Strategy at SMP Muhammadyah 9 Boarding School Tanggulangin: Strategi Pemasaran Pendidikan di SMP Muhammadyah 9 Boarding School Tanggulangin - Sahlan; Rahmawati, Imelda Dian (Indonesian Journal of Innovation Studies, 2026)
General Background: Educational marketing strategy drives public trust and institutional sustainability across modern academic service providers. Specific Background: Islamic boarding schools require targeted promotional frameworks to maintain competitive advantages. Knowledge Gap: However, field execution often lacks comprehensive integration of marketing mix elements within faith-based boarding environments. Aims: This study analyzes the educational marketing mix strategy implemented at SMP Muhammadiyah 9 Boarding School Tanggulangin. Results: Findings demonstrate optimized student recruitment through integrated promotional channels, specialized academic programs, and diversified extracurricular activities. Novelty: This research highlights unique marketing mix adaptation within a Muhammadiyah-affiliated boarding school context. Implications: Strategic service delivery and active community engagement foster sustainable enrollment growth and educational quality. Key Findings Highlights Integrated marketing promotion optimizes student admission programs and community engagement. Holistic curricular and extracurricular offerings strengthen institutional reputation. Strategic mix adoption enhances competitive advantage in Islamic boarding education. Keywords: Educational Marketing Mix, Student Recruitment, Boarding School, Educational Quality, Marketing Promotion